Solar cell and preparation method thereof
The hydroxylation treatment of CMP fine-drawing and the mixture of H2O2, HCl and H2O is solved by solving the problem of excessive SiOx content caused by the oxidation treatment of the back surface of the P+Poly layer, improving the passivation performance of the Al2O3 film, and improving the solar cell Efficiency, and environmental protection and cost reduction.
Patent Information
- Application Number
- CN202310800755.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The oxidation treatment on the back surface of the existing P+Poly layer leads to excessive SiOx content in the Al2O3 film, reducing the passivation performance of the Al2O3 film, and the thermal nitric acid oxidation reaction is not environmentally friendly, increasing the treatment cost.
Using CMP fine-drawing and a mixture of H2O2, HCl and H2O for hydroxylation, to form an ultra-thin SiOx layer, occupying oxygen vacancy, providing a more uniform interface, making the Al2O3 film grow more uniformly, reducing SiOx content, and increasing the bluntness of Al2O3 film .
The SiOx content in the Al2O3 film is significantly reduced, the passivation performance is improved, the efficiency of solar cells is improved, and the method is environmentally friendly and the processing cost is reduced.
Smart Images

Figure CN119230650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a solar cell and a preparation method thereof. Background Art
[0002] In a P-type solar cell (such as a P-PERC cell, a P-TOPCon cell), an n+ emitter is prepared by doping phosphorus on the front side of a silicon wafer, and a P+ emitter (such as a P+Poly layer) is prepared on the back side of the silicon wafer.
[0003] Among them, a negatively charged polar material film (i.e., Al2O3 film) is usually prepared on the back of the P+Poly layer as a passivation film of the P+Poly layer. The Al2O3 film is usually prepared by the ALD (atomic layer deposition) method, and its preparation raw material is TMA (trimethylaluminum). The oxygen in the preparation process is generally obtained in the form of water oxygen, that is, water is used as the source of oxygen in the Al2O3 film. When preparing the Al2O3 film, due to the presence of oxygen vacancies on the back surface of the P+Poly layer, the P+Poly layer will also be oxidized while the Al2O3 film is generated, thereby generating a certain amount of SiO x (i.e. silicon oxide). SiO x The band gap width of SiO exceeds 4.5eV and reaches 4.6eV. It is an insulator. x The presence of will increase the series resistance, reduce the Al2O3 content in the Al2O3 film, and thus weaken the passivation performance of the Al2O3 film. Moreover, since crystalline silicon is a hydrophobic material, the P+Poly layer will form a discontinuous, uneven, and uneven SiO x film, which will further increase the SiO x , increase SiO x The negative impact brought about.
[0004] The existing processing method is as shown in CN108878570A, using NAOS (Nitric Acid Oxide Silicon, thermal nitric acid oxidation such as the silicon surface of the P+Poly layer) in BOE (Buffered Oxide Etch) to prepare a layer of SiO on the back surface of the P+Poly layer in advance. x , in order to reduce the SiO in the subsequent preparation of Al2O3 film by ALD method x The negative impact of disordered growth; and by growing SiO x To improve the hydrophobicity of the back surface of the P+Poly layer, when the Al2O3 film is subsequently grown, the oxygen from water in the reactant is allowed to be released on the non-hydrophobic SiO xThe surface is evenly covered, so that the Al2O3 film grows evenly. Wherein, hot nitric acid refers to nitric acid at a temperature of 35-55°C (such as 40°C).
[0005] However, the existing processing method still has the following defects:
[0006] 1. The back surface of the P+Poly layer is not flat enough. The uneven back surface of the P+Poly layer will produce more silicon dangling bonds, bring more oxygen vacancies, and make the subsequent thermal nitric acid oxidation of the back surface of the P+Poly layer produce SiO x Too thick.
[0007] 2. Although thermal nitric acid oxidation is used to prepare SiO x This is a self-terminating reaction, but the SiO generated by this treatment method x Thicker, resulting in SiO in the Al2O3 film x The percentage content will exceed 50%, which further increases the resistance of the Al2O3 film, reduces the content of Al2O3 in the passivation film, and reduces the passivation performance of the passivation film.
[0008] 3. Nitric acid contains N, which easily forms nitrogen oxides. At a time when environmental protection requirements are more stringent, subsequent treatment of wastewater containing nitrogen oxides will bring higher treatment costs. Summary of the invention
[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a solar cell and a method for preparing the same.
[0010] Based on this, the present invention discloses a method for preparing a solar cell, comprising the following steps:
[0011] S1, doping and diffusing the textured silicon wafer to prepare an n+ emitter on the front side of the silicon wafer; wherein the diffusion forms phosphorus silicon glass on both the front and back sides of the silicon wafer;
[0012] S2, performing single-side pickling on the back of the silicon wafer to remove the phosphorus silicon glass on the back of the silicon wafer;
[0013] S3, performing alkali polishing on the back of the silicon wafer to form a planar morphology on the back of the silicon wafer and retaining the phosphorus silicon glass on the front of the silicon wafer;
[0014] S4, sequentially preparing a tunneling layer and a P+Poly layer on the back side of the silicon wafer;
[0015] S5, using silicon polishing liquid to perform CMP fine polishing on the back surface of the P+Poly layer, so that the plane morphology of the back surface of the P+Poly layer becomes flat and smooth;
[0016] S6, first cleaning the silicon wafer to remove organic matter, impurities and phosphorus silicon glass on the front surface of the silicon wafer, and then using a treatment liquid to hydroxylate the back surface of the P+Poly layer to make the back surface of the P+Poly layer hydrophilic; wherein the treatment liquid is prepared by water, H2O2 and HCl in a volume ratio of 7-13:1:2;
[0017] S7, passivating the silicon wafer to form a front passivation film on the front of the n+ emitter, and forming a back passivation film on the back surface of the P+Poly layer; wherein the back passivation film comprises an Al2O3 film deposited on the back surface of the P+Poly layer by atomic layer deposition;
[0018] S8. Metallize the front and back sides of the silicon wafer to obtain front metal electrodes and back metal electrodes, respectively.
[0019] Preferably, in step S5, the silicon polishing liquid has a raw material ratio, calculated by volume fraction, of:
[0020]
[0021] Water balance.
[0022] Further preferably, in step S3 and step S5, the process conditions of CMP fine polishing are: the rotation speed of the polishing disc is 26-33r / min, the temperature is 25-30°C, the polishing rate is 0.8-1um / min, and the polishing pressure is 0.8-1.2N / cm 2 , time is 10-20s, the polishing pad is a non-woven fabric with fluff, and the polishing amount is 10-20nm.
[0023] Preferably, in step S6, the treatment liquid is water, H2O2 and HCl prepared in a volume ratio of 10:1:2, the water is deionized water, and the treatment time is 150-200s;
[0024] The silicon wafer is cleaned in sequence with a hydrogen peroxide solution, a mixture of HCl and HF to remove organic matter and impurities remaining on the surface of the silicon wafer, the phosphorus silicon glass retained on the front side, and an annealed oxide layer formed by annealing.
[0025] Preferably, in step S4, after preparing the tunneling layer, an amorphous silicon layer doped with a P-type material is prepared on the back of the tunneling layer, and then the silicon wafer is annealed to obtain a P+Poly layer;
[0026] Wherein, the annealing treatment temperature is 800-1000°C and the time is 0.5-1.5h.
[0027] Preferably, in step S3, the alkali polishing is performed using a KOH solution, wherein the KOH solution is prepared by mixing water and KOH in a volume ratio of 18-25:1; the alkali polishing time is 250-350s and the temperature is 45-65°C.
[0028] Preferably, step S2 further includes using the single-sided pickling to remove the wrap-around plating caused by doping diffusion at the edge of the silicon wafer;
[0029] In step S2, the single-side pickling is performed using an HF solution, wherein the HF solution is prepared by mixing HF and water in a volume ratio of 1:1.5-2.
[0030] Preferably, in step S1, before doping and diffusion, the silicon wafer is textured to form a textured light-trapping structure on the surface of the silicon wafer. The silicon wafer is preferably a P-type silicon wafer.
[0031] Preferably, in step S7, the back passivation film further comprises a back silicon nitride film deposited on the back of the Al2O3 film; the front passivation film is and a front silicon nitride film; the back passivation film is a back silicon nitride film.
[0032] More preferably,
[0033] The present invention also discloses a solar cell, which is prepared by the above-mentioned method for preparing a solar cell of the present invention.
[0034] Among them, CMP (Chemical Mechanical Polishing) can prepare an ultra-flat atomic-level surface. The present invention is combined with hydroxylation treatment to form an ultra-thin SiO2 layer with a thickness of much less than 1nm and a hydroxyl group on the outer surface on the back surface of the P+Poly layer. x , to occupy the oxygen vacancies on the back surface of the P+Poly layer, and provide a more hydrophilic interface when the Al2O3 film is grown by the subsequent ALD method, so that the growth of the Al2O3 film is more uniform, thereby greatly reducing the SiO x content, and improve the flatness and quality of the Al2O3 film and its passivation performance.
[0035] In P-TOPCon and P-PERC cells, after the P+Poly layer is prepared, the back of the P+Poly layer is subjected to CMP polishing to make the back surface of the P+Poly layer smoother and reduce the empty bonds on the back surface of the P+Poly layer as much as possible; then, the back surface of the P+Poly layer is subjected to hydroxylation surface modification to occupy the oxygen vacancies on the back surface of the P+Poly layer in advance, and an ultra-thin SiO layer with a thickness of much less than 1nm and hydroxyl groups on the outer surface is grown in advance under controlled conditions. x (See Figure 3 ) to prevent SiOx It can reduce the negative effects caused by excessive thickness, and hydroxylate the back surface of the P+Poly layer, improve the hydrophilicity of its back surface, and make the growth of the Al2O3 film more uniform.
[0036] It should be noted that since water is needed as a source of oxygen in the ALD method, the hydrophobic surface will cause poor contact between the reactants and the back surface of the P+Poly layer, resulting in uneven growth of the Al2O3 film. After the back surface of the P+Poly layer is hydroxylated, the hydroxyl groups on the back surface of the P+Poly layer (specifically, the ultra-thin SiO2O3 layer with hydroxyl groups on the back surface of the P+Poly layer) x ) can form a physical property of short-term bonding with water molecules through hydrogen bonds, so that water molecules adhere to the back surface of the P+Poly layer, thus forming a three-phase equilibrium state of liquid water molecules, air and solid on a certain surface area of the back surface of the P+Poly layer, such as Figure 1 As shown:
[0037] Among them, γ represents the interface energy, the subscript represents the type of interface, S represents solid (i.e. P+Poly layer), L represents liquid, G represents gas, and θ represents the contact angle. Figure 2 , based on the principle of virtual work, after the three-phase contact line moves dx displacement, the SL interface and LG interface will expand, and the SG interface will shrink. Therefore, according to the definition of interface energy, the interface energy change can be expressed as formula (1):
[0038] dE=(γ SL -γ SG )dxΔL+γ LG cosθdxΔL (1)
[0039] Because the droplet is in equilibrium at this time, dE / dx=0 is substituted into equation (1) and simplified to obtain the following equation (2):
[0040] cosθ=(γ SG -γ SL ) / γ LG (2)
[0041] According to the size of the contact angle θ, the hydrophilicity and hydrophobicity can be summarized as:
[0042] 0≤θ<90° is a hydrophilic surface; 90°<θ<150° is a hydrophobic surface; 150°≤θ≤180° is a super hydrophobic surface.
[0043] The back surface of the P+Poly layer is hydroxylated by using different treatment solutions to change the interface energy of the back surface of the P+Poly layer. After the hydroxylation treatment, most of the Si on the back surface of the P+Poly layer is terminated with Si-O bonds, that is, an amorphous SiO is formed on the back surface of the P+Poly layer. xstructure, and the Si on the other part of the back surface of the P+Poly layer is terminated with Si-OH bonds (such as Figure 3 As shown in the figure, the high γ SG to adsorb water molecules.
[0044] The existing treatment method is to use hot nitric acid to treat the back surface of the P+Poly layer, which is not environmentally friendly and produces SiO x Also thicker.
[0045] Furthermore, when different treatment solutions are used to treat the silicon surface (such as the P+Poly layer surface), the contact angles are also different. The contact angles of the surfaces treated with different treatment solutions are shown in the following table:
[0046]
[0047]
[0048] After treatment with ammonia and hydrogen peroxide, the contact angle is the smallest, and the most hydroxyls are formed on the surface; however, ammonia treatment easily corrodes the P+Poly layer, resulting in by-products, and ammonia and hydrogen peroxide are volatile, so the pH value is easy to change, and the pH value has a great influence on the treatment results (the pH value is too large or too small, and the solution leads to poor surface hydroxylation). The use of sulfuric acid is even more dangerous. The present invention uses a mixed solution of H2O2, HCl and H2O as a treatment liquid, which can not only form the better hydroxylated hydrophilic interface we need on the back surface of the P+Poly layer, but also clean the surface pollutants generated by the previous step of CMP polishing (the chloride ions in hydrochloric acid can combine with impurity metal ions to form complexes and be cleaned and removed). Therefore, the present invention uses a combination of CMP polishing and post-treatment liquid (i.e., a mixed solution of H2O2, HCl and H2O) to treat the back surface of the P+Poly layer to hydroxylate the surface, which can make the ultra-thin SiO2 formed by hydroxylation x and the SiO in the Al2O3 film prepared by the subsequent ALD method x The total content dropped to less than 30%, which is significantly less than the SiO x 54% of the total content.
[0049] Compared with the prior art, the present invention has at least the following beneficial effects:
[0050] The present invention treats the back surface of the P+Poly layer by first CMP polishing and then surface hydroxylation with a post-treatment solution (i.e., a mixed solution of H2O2, HCl and H2O), so that the ultra-thin SiO2 formed by hydroxylation can be x and the SiO in the Al2O3 film prepared by the subsequent ALD method x The total content dropped to less than 30%, which is significantly less than the SiOx The total content is 54%, so the battery prepared by the present invention enhances the passivation performance of the passivation film (especially the Al2O3 film), thereby improving the battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 Schematic diagram of the three-phase equilibrium state of liquid water molecules, air and P+Poly layer solid.
[0052] Figure 2 Schematic diagram of the change in interfacial energy after the three-phase contact line of liquid water molecules, air and P+Poly layer solid moves.
[0053] Figure 3 Schematic diagram of the bonding molecular structure on the back surface of the P+Poly layer after hydroxylation treatment.
[0054] Figure 4 It is a comparative data chart of the component contents of the Al2O3 films of Example 1, Comparative Example 1 and Comparative Example 2.
[0055] Figure 5 The PL brightness comparison data of Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG.
[0056] Figure 6 It is a comparative data chart of the battery efficiency of Example 1, Comparative Example 1 and Comparative Example 2.
[0057] Figure 7 This is a schematic diagram of the cross-sectional structure of a solar cell in Example 1.
[0058] Explanation of the accompanying drawings: silicon wafer 1; n+ emitter 2; front silicon nitride film 3; front metal electrode 4; tunneling layer 5; P+Poly layer 6; Al2O3 film 7; back silicon nitride film 8; back metal electrode 9. DETAILED DESCRIPTION
[0059] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0060] Example 1
[0061] A method for preparing a solar cell in this embodiment, see Figure 7 , comprising the following steps in sequence:
[0062] Step 1, texturing: texturing is performed on the silicon wafer 1 to form a textured light-trapping structure on the surface of the silicon wafer 1. The silicon wafer is preferably a P-type silicon wafer.
[0063] In one example of this embodiment, the solution used for the texturing treatment is a mixed solution of water: KOH: ADD configured at a volume ratio of 200-250: 3: 1. For example, in the mixed solution used for the texturing treatment, the volume ratio of water: KOH: ADD is preferably 230: 3: 1. The water used in the mixed solution is preferably deionized water.
[0064] Specifically, ADD is an additive, such as isopropyl alcohol; the main function of ADD is to promote the reaction between the base (such as KOH) and the surface of the silicon wafer 1, and the peeling of the reaction product.
[0065] Of course, in other examples of this embodiment, other existing solutions may also be used to texture the surface of the silicon wafer 1 .
[0066] Step 2: Diffusion: doping and diffusion are performed on the silicon wafer 1 to prepare an n+ emitter 2 on the front side of the silicon wafer 1 .
[0067] The doping source of the doping diffusion is preferably a phosphorus source, such as POCl 3. The doping diffusion process of the phosphorus source is a prior art, so it will not be described in detail.
[0068] During the doping diffusion process, in addition to forming an n+ emitter 2 on the front side of the silicon wafer 1 , phosphosilicate glass (PSG) is also formed on the front side of the n+ emitter 2 and the back side of the silicon wafer 1 , and wrap-around plating is formed on the edge of the silicon wafer 1 .
[0069] Step 3, single-side pickling: single-side pickling is performed on the doped and diffused silicon wafer 1 to remove the phosphosilicate glass on the back of the silicon wafer 1 and to remove the wrap-around plating on the edge of the silicon wafer 1 .
[0070] In an example of this embodiment, a single-side pickling of the doped and diffused silicon wafer 1 is performed using an HF solution, wherein the HF solution is prepared by mixing HF and water in a volume ratio of 1:1.5-2.
[0071] For example, the volume ratio of HF to water in the HF solution is 1:1.8. In practice, the water used in the HF solution is preferably deionized water.
[0072] Step 4, polishing: alkaline solution (i.e., alkali solution) is used to perform alkaline polishing on the back side of the silicon wafer 1 to form a smooth plane morphology on the back surface of the silicon wafer 1; and the PSG on the front side of the silicon wafer 1 is retained to use the PSG as a protective layer for subsequent CMP fine polishing.
[0073] The PSG on the front side of the silicon wafer 1 is retained, which can protect the n+ emitter 2 on the front side of the silicon wafer 1 to prevent the n+ emitter 2 from being damaged during CMP polishing, and does not require additional preparation of a protective layer or mask, and does not add additional steps.
[0074] In one example of this embodiment, a KOH solution is used to perform alkali polishing on the back side of the silicon wafer 1. The KOH solution is prepared by mixing water and KOH at a volume ratio of 18-25:1. The alkali polishing time is 250-350 seconds, and the alkali polishing temperature is 45-65° C. For example, the volume ratio of water to KOH in the KOH solution used for alkali polishing is 23:1, the alkali polishing time is 305 seconds, and the alkali polishing temperature is 50° C.
[0075] Step 5, preparation of TOPCon structure (passivation contact structure): a tunneling layer 5 and an amorphous silicon layer doped with p-type material are sequentially prepared on the back side of the silicon wafer 1 .
[0076] The preparation method of the TOPCon structure includes but is not limited to one or more of low-pressure chemical deposition, ion implantation or physical deposition. The preparation process can refer to the preparation steps of the existing TOPCon battery, so it will not be repeated here.
[0077] Step 6, annealing: annealing the silicon wafer 1 so that the amorphous silicon layer is crystallized during the annealing process to become a Poly layer (i.e., polycrystalline silicon layer), and the doped atoms in the doped p-type material are activated to obtain a P+Poly layer 6.
[0078] Specifically, the annealing temperature is 800-1000° C., and the holding time is 0.5-1.5 h.
[0079] In an example of this embodiment, the annealing temperature is 910° C. and the holding time is 0.9 h.
[0080] After the annealing treatment in step 6, the thickness of the obtained P+Poly layer 6 is controlled to be 110-130 nm, for example, 120 nm.
[0081] Step 7, CMP (chemical mechanical polishing) fine polishing: Under the action of the polishing liquid and the polishing disk, the back side of the P+Poly layer 6 is subjected to chemical mechanical polishing to make the back surface of the P+Poly layer 6 more flat and smooth.
[0082] The existing CMP process includes three stages: rough polishing, fine polishing and fine polishing, which is time-consuming. After the alkaline polishing in step 4, the surface of the P+Poly layer 6 basically maintains a planar morphology, so only CMP fine polishing is performed in step 7, which can not only obtain the back surface of the P+Poly layer 6 with an ideal flatness, but also save time.
[0083] Specifically, in step 7, a silicon polishing solution is used for chemical mechanical polishing, and the polishing time of the chemical mechanical polishing is 10-20 seconds (for example, 15 seconds). The formula of the silicon polishing solution is as follows:
[0084]
[0085] The water in the silicon polishing liquid is preferably deionized water.
[0086] Specifically, in the CMP fine polishing of step 7, the rotation speed of the polishing disk is 26-33r / min, the temperature is maintained at 25-30°C, the polishing rate is 0.8-1um / min, and the polishing pressure is 0.8-1.2N / cm 2 The polishing pad is made of non-woven fabric with fluff, and the polishing amount of CMP fine polishing is 10-20nm.
[0087] In one example of this embodiment, the formula of the silicon polishing liquid is:
[0088]
[0089] In one example of this embodiment, in the CMP fine polishing of step 7, the rotation speed of the polishing disk is 28 r / min, the temperature is maintained at 27°C, the polishing rate is 0.9 um / min, and the polishing pressure is 0.9 N / cm 2 , the polishing pad should be made of non-woven fabric with fluff.
[0090] Step 8, cleaning: Clean the silicon wafer 11 to remove the organic matter, impurities (such as metal impurities) remaining on the surface of the silicon wafer 1, the annealed oxide layer formed by annealing, and the PSG retained on the front side, and then perform hydroxylation treatment on the back surface of the P+Poly layer 6 to make the back surface of the P+Poly layer 6 hydrophilic.
[0091] Specifically, the silicon wafer 1 is cleaned with a hydrogen peroxide solution and a mixture of HCl and HF in sequence, and then the back surface of the P+Poly layer 6 is hydroxylated with a treatment solution to reduce the contact angle of the back surface of the P+Poly layer 6 and make the back surface of the P+Poly layer 6 hydrophilic, thereby reducing the SiO2 in the Al2O3 film 7 prepared by ALD. x Content provides conditions.
[0092] In one example of this embodiment, the mixed solution of HCl and HF is prepared by water: HF: HCl in a volume ratio of 10-15:3:1, the water is preferably deionized water, and the cleaning time using the mixed solution of HCl and HF is controlled to be 200-300s.
[0093] For example, the volume ratio of water: HF: HCl in the mixed solution of HCl and HF is 13:3:1, and the cleaning time using the mixed solution of HCl and HF is controlled at 235 s.
[0094] The mixed solution of HCl and HF is mainly used to remove the front PSG retained in step 4 to protect the n+ emitter 2 .
[0095] In one example of this embodiment, the volume ratio of the treatment liquid used for the hydroxylation treatment is water: H2O2: HCl = 7-13: 1: 2, the water is preferably deionized water, and the treatment time is controlled at 150-200s.
[0096] For example, the volume ratio of the treatment solution used in the hydroxylation treatment is water: H2O2: HCl = 10:1:2, and the treatment time is controlled at 158 s.
[0097] Step 9, coating: Al2O3 film 7 and back silicon nitride film 8 are sequentially prepared on the back side of the hydroxylated P+Poly layer 6, and front silicon nitride film 3 is prepared on the front side of the n+ emitter 2.
[0098] In step 9, TMA (trimethylaluminum) is used as a raw material and the ALD (atomic layer deposition) method is used to prepare the Al2O3 film 7. SiH4 and NH3 are used as precursor gases to prepare the front silicon nitride film 3 and the back silicon nitride film 8, so that the precursor gas can release atomic H to hydrogen passivate the silicon wafer 1. The coating process of step 9 can refer to the prior art, so it is not described in detail.
[0099] Step 10, metallization: metallization treatment is performed on the silicon wafer 1 to form a front metal electrode 4 contacting the n+ emitter 2 on the front side of the silicon wafer 1 , and a back metal electrode 9 contacting the P+ Poly layer 6 on the back side of the silicon wafer 1 .
[0100] In practice, metal paste (such as silver paste) is printed on a local area of the surface of the silicon wafer 1 by screen printing and sintered to form the front metal electrode 4 and the back metal electrode 9. The metallization process is a prior art and will not be described in detail.
[0101] After processing in step 10, the solar cell of this embodiment can be obtained. The structure of the solar cell is as follows: Figure 7 shown.
[0102] Comparative Example 1
[0103] A solar cell and a preparation method thereof in this comparative example refer to Example 1, and the difference between the solar cell and Example 1 is that:
[0104] The back surface of the P+Poly layer 6 is first subjected to CMP polishing in step 7 and then subjected to hydroxylation after cleaning in step 8 (hereinafter referred to as CMP polishing + hydroxylation treatment) in Example 1, and is replaced by the existing treatment method (i.e., the back surface of the P+Poly layer 6 is oxidized with hot nitric acid at 40°C to prepare SiO on the back surface of the P+Poly layer 6 in advance). x ).
[0105] Comparative Example 2
[0106] A solar cell and a preparation method thereof in this comparative example refer to Example 1, and the difference between the solar cell and Example 1 is that:
[0107] The step 7 of performing CMP polishing on the back surface of the P+Poly layer 6 in the embodiment 1 is omitted, and only the hydroxylation treatment after cleaning in the step 8 of the embodiment 1 is retained.
[0108] Performance Testing
[0109] 1. See Figure 4 The battery samples treated with CMP polishing + hydroxylation in Example 1, the battery samples treated with the existing treatment method (Comparative Example 1), and the battery samples treated with hydroxylation only (Comparative Example 2) were tested by XPS peak fitting. It was found that:
[0110] For the sample of Comparative Example 1, the content of Al2O3 in the aluminum oxide passivation film (i.e., Al2O3 film) prepared by the ALD method is relatively low, and the unexpected product SiO x The content is higher.
[0111] For the sample of comparative example 2, the back surface of the P+Poly layer 6 can be hydroxylated to become a hydrophilic interface, which increases the reaction sites on the back surface, is beneficial to the adsorption and reaction of the precursor, and can form a controlled SiO layer on the back surface before the ALD method. x , effectively blocking the oxygen vacancies on the back surface of the P+Poly layer 6, increasing the Al2O3 content in the passivation film layer and improving the passivation performance.
[0112] For the sample treated with CMP polishing + hydroxylation in Example 1, the back surface of the P+Poly layer 6 is further flattened by CMP polishing + hydroxylation, thereby avoiding the formation of ultra-thin SiO x The "island-like" growth pattern in the early stage of growth significantly shortens the period required to reach a stable growth state, accelerates the growth rate and improves the growth quality.
[0113] 2. See Figure 5 The PL brightness of the battery sample treated with CMP polishing + hydroxylation in Example 1 is compared with that of the battery sample treated with the existing treatment method (Comparative Example 1) and the battery sample treated with hydroxylation only (Comparative Example 2). It is found that:
[0114] Compared with Comparative Example 1, the PL brightness of the sample of Comparative Example 2 is increased by 0.67%, and compared with Comparative Example 2, the PL brightness of the sample treated by CMP polishing + hydroxylation in Example 1 is increased by 2.31%. Therefore, compared with Comparative Example 1, the final PL brightness of the sample treated by CMP polishing + hydroxylation in Example 1 is increased by nearly 3%, so the battery obtained by the preparation method of Example 1 can greatly improve the passivation performance of its Al2O3 film 7.
[0115] 3. See Figure 6 The battery efficiency of the battery sample treated with CMP polishing + hydroxylation in Example 1 was compared with that of the battery sample treated with the existing treatment method (Comparative Example 1) and the battery sample treated with hydroxylation only (Comparative Example 2). It was found that:
[0116] Compared with Comparative Example 1, the battery efficiency of the sample of Comparative Example 2 is increased by 0.04%, and compared with Comparative Example 2, the battery efficiency of the sample treated by CMP polishing + hydroxylation in Example 1 is increased by 0.07%. Therefore, compared with Comparative Example 1, the battery efficiency of the sample treated by CMP polishing + hydroxylation in Example 1 is increased by 0.11% in total, and the battery efficiency is significantly improved.
[0117] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0118] The technical solution provided by the present invention is introduced in detail above. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a solar cell, characterized in that: The steps include: S1, doping and diffusing the textured silicon wafer to prepare an n+ emitter on the front side of the silicon wafer; wherein the diffusion forms phosphorus silicon glass on both the front and back sides of the silicon wafer; S2, performing single-side pickling on the back of the silicon wafer to remove the phosphorus silicon glass on the back of the silicon wafer; S3, performing alkali polishing on the back of the silicon wafer to form a planar morphology on the back of the silicon wafer and retaining the phosphorus silicon glass on the front of the silicon wafer; S4, sequentially preparing a tunneling layer and a P+Poly layer on the back side of the silicon wafer; S5, using silicon polishing liquid to perform CMP fine polishing on the back surface of the P+Poly layer, so that the plane morphology of the back surface of the P+Poly layer becomes flat and smooth; S6, first cleaning the silicon wafer to remove organic matter, impurities and phosphorus silicon glass on the front surface of the silicon wafer, and then using a treatment liquid to hydroxylate the back surface of the P+Poly layer to make the back surface of the P+Poly layer hydrophilic; wherein the treatment liquid is prepared by water, H2O2 and HCl in a volume ratio of 7-13:1:2; S7, passivating the silicon wafer to form a front passivation film on the front of the n+ emitter, and forming a back passivation film on the back surface of the P+Poly layer; wherein the back passivation film comprises an Al2O3 film deposited on the back surface of the P+Poly layer by atomic layer deposition; S8. Metallize the front and back sides of the silicon wafer to obtain front metal electrodes and back metal electrodes, respectively.
2. The method for preparing a solar cell according to claim 1, characterized in that: In step S5, the silicon polishing liquid has a raw material ratio, calculated by volume fraction, of: Water balance.
3. A method for preparing a solar cell according to claim 1 or 2, characterized in that: In step S3 and step S5, the process conditions of CMP fine polishing are: the rotation speed of the polishing disc is 26-33r / min, the temperature is 25-30°C, the polishing rate is 0.8-1um / min, and the polishing pressure is 0.8-1.2N / cm 2 , time is 10-20s, the polishing pad is a non-woven fabric with fluff, and the polishing amount is 10-20nm.
4. The method for preparing a solar cell according to claim 1, characterized in that: In step S6, the treatment liquid is prepared by water, H2O2 and HCl in a volume ratio of 10:1:2, the water is deionized water, and the treatment time is 150-200s; The silicon wafer is cleaned in sequence with a hydrogen peroxide solution, a mixture of HCl and HF to remove organic matter and impurities remaining on the surface of the silicon wafer, the phosphorus silicon glass retained on the front side, and an annealed oxide layer formed by annealing.
5. The method for preparing a solar cell according to claim 1, characterized in that: In step S4, after the tunneling layer is prepared, an amorphous silicon layer doped with a P-type material is prepared on the back of the tunneling layer, and then the silicon wafer is annealed to obtain a P+Poly layer; Wherein, the annealing treatment temperature is 800-1000°C and the time is 0.5-1.5h.
6. The method for preparing a solar cell according to claim 1, characterized in that: In step S3, the alkali polishing is performed using a KOH solution, wherein the KOH solution is prepared by mixing water and KOH in a volume ratio of 18-25:1; the alkali polishing time is 250-350s and the temperature is 45-65°C.
7. The method for preparing a solar cell according to claim 1, characterized in that: Step S2 also includes using the single-sided pickling to remove the wrap-around plating caused by doping diffusion at the edge of the silicon wafer; In step S2, the single-side pickling is performed using an HF solution, wherein the HF solution is prepared by mixing HF and water in a volume ratio of 1:1.5-2.
8. The method for preparing a solar cell according to claim 1, characterized in that: In step S1, before doping and diffusion, the silicon wafer is textured to form a textured light-trapping structure on the surface of the silicon wafer.
9. The method for preparing a solar cell according to claim 1, characterized in that: In step S7, the back passivation film also includes a back silicon nitride film deposited on the back of the Al2O3 film; the front passivation film is and a front silicon nitride film; the back passivation film is a back silicon nitride film.
10. A solar cell, characterized in that: The solar cell is prepared by the method for preparing the solar cell according to any one of claims 1 to 9.
